Women face a labyrinth: an examination of metaphors for women leaders - Carli, Linda L.; Eagly, Alice H. (Gender in management, 2016)
Purpose The purpose of this paper is to explore the most common general metaphors for women’s leadership: the glass ceiling, sticky floor and the labyrinth. The authors discuss the strengths and weaknesses of these metaphors for characterizing women’s current situation as leaders. Design/methodology/approach In addition to reviewing the literature on the status of women leaders, the authors also discuss recent research on the power of metaphor to illustrate concepts and influence social judgments. Findings The authors conclude that the labyrinth is the most useful metaphor for women leaders, because although there has been slow steady improvement in women’s access to leadership, women continue to face challenges that men do not face: gender stereotypes that depict women as unsuited to leadership, discrimination in pay and promotion, lack of access to powerful mentors and networks and greater responsibility for childcare and other domestic responsibilities. Practical implications Although the glass ceiling metaphor implies that women face obstacles once they have risen to very high levels of leadership and the sticky floor metaphor implies that women are prevented from any advancement beyond entry level, the labyrinth reflects the myriad obstacles that women face throughout their careers. Originality/value The labyrinth metaphor not only acknowledges these challenges but also suggests that women can advance to very high levels of leadership.